(untitled) (University Heart Journal, 2015)
In acute myocardial infarction (AMI), generation of free radicals contribute to its pathogenesis. We evaluated the extent of oxidative stress and its amelioration in AMI patients after regular treatment and assessed its association with risk factors like dyslipidemia and diabetes mellitus (DM). Plasma MDA level increased (p<0.001) and erythrocyte GSH and plasma vitamin E levels decreased (p<0.001) in AMI patients. On the 5th day of regular treatment MDA level reduced (p<0.001) and erythrocyte GSH and vitamin E levels increased (p<0.001). The rise in MDA and fall in vitamin E levels were significant (p<0.001) in patients with both dyslipidemia and DM in comparison to patients without dyslipidemia or DM. It is concluded that an imbalance exists between oxidant and antioxidant molecules in AMI patients which shifts towards oxidative side and treatment restores this balance. There may be some association between oxidative stress in AMI and risk factors like dyslipidemia and diabetes mellitus. University Heart Journal Vol. 10, No. 2, July 2014; 60-65